Promising electrode material of Fe3O4 nanoparticles decorated on V2O5 nanobelts for high-performance symmetric supercapacitors. Issue 4 (15th February 2023) - Akkinepally, Bhargav; Neelakanta Reddy, I.; Lee, Cheonghwan; Jo Ko, Tae; Srinivasa Rao, P.; Shim, Jaesool
Abstract: Bundled V2 O5 nanobelts decorated with Fe3 O4 nanoparticles (F3V nanostructures) were successfully synthesized to develop a low-cost electrode material for energy storage applications. The synthesized samples were subjected to structural, morphological and electrochemical studies. The Fe3 O4 nanoparticles decorated over bundled V2 O5 nanobelts exhibited better electrochemical properties than the pristine Fe3 O4 nanoparticles and V2 O5 nanobelts. The electrochemical behavior of the fabricated electrodes was investigated in an electrolyte of 3 M KOH, demonstrated an exceptional specific capacity values of 750.1, 660.3, and 1519 F g –1 for V2 O5, Fe3 O4, and F3V respectively at a current density of 15 A g –1 . The assembled F3V symmetric supercapacitor (SSC) device exhibited an excellent specific capacitance of 93 F g –1 at a current density of 0.5 A g –1, delivering energy and power densities of 13 Wh.kg –1 and 1530 W kg –1, respectively, and superior long-term cycling stability of ∼84% capacity retention over 5000 galvanostatic charge–discharge cycles. These findings demonstrate the extraordinary electrochemical characteristics of the F3V nanostructures, indicating their potential use in energy storage applications.